Network for the Large-Scale Integration of Renewable Energies in Electrical Systems (RIBIERSE-CYTED, 723RT0150): Results for 2023 - Medina-Quesada, María Ángeles; Serra, Federico Martin; Baier-Fuentes, Carlos Rodrigo; Montoya-Giraldo, Oscar Danilo; Soares, Joao André Pinto; França, Bruno Wanderley; Andrade-Rengifo, Fabio; Hernández, Jesús de la Casa (Ingeniería, 2024)
The RIBIERSE-CYTED network, i.e., the network for the large-scale integration of renewable energies in electrical systems (723RT0150) (2023-2026) is a hub for researchers and technologists belonging to Ibero-American universities, companies, and local administrations. This network promotes cross-training, mobility between centers, and the dissemination and implementation of technical and training activities aimed at analyzing and developing opportunities for the maximal integration of renewable resources, seeking a more sustainable energy model while allowing for the increased use of renewable resources and electric mobility (e-mobility).